Numerical simulation of heat transfer in MHD stagnation point flow of Cross fluid model towards a stretched surface - Hayat, T.; Khan, M. Ijaz; Tamoor, M.; Waqas, M.; Alsaedi, A. (Results in physics, 2017)
The present investigation studies heat transfer in MHD stagnation point flow of Cross fluid over a stretched surface. A Cross fluid is a kind of generalized Newtonian liquid whose viscosity relies on shear rate. Fluid is electrically conducting in the presence of an applied magnetics fluids. System of ordinary differential equations is obtained by appropriate transformation. The flow equations are solved with the help of Runga-Kutta-Fehlberg method. Convergent series solutions are computed for the resulting nonlinear differential system. Impact of different parameters on the velocity and temperature profiles is studied. It is observed that velocity distribution decreases for larger values of Weissenberg number. However temperature decays for rising values of Prandtl number. Further computation for surface drag force and heat transfer rate are presented and discussed through numerical data.